Livro de nutrição na prevenção do câncer de pele - Batista, Franciele Cristina [UNIFESP] (2021)
Introduction: Skin cancer is an important topic in public health, due to its high morbidity and mortality. Basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) are the most prevalent skin cancers. The high sun exposure of the population and workers with external activities is a relevant health issue in Brazil and in the world. There are foods with certain dietary components such as antioxidants, carotenoids, flavonoids, probiotics and fatty acids ômega-3, which can contribute to the protection of the skin against damage caused by ultraviolet radiation (UVR). In this way, the idea of a “Book on nutrition in the prevention of skin cancer” in printed and digital form (e-book) aroused as purpouse. Objective: Develop and validate a nutrition book on skin cancer prevention for healthcare professionals and the lay pulic. Method: A “Nutrition book on skin cancer prevention” was elaborated and validated by means of the Delphi Technique and the Content Validity Index. Results: As the literature found, five chapters of the book were defined, with the consecutive themes: “Epidemiology of Skin Cancer”, “Epigenetics of Skin Cancer”, “Handling Tips, Food Preparation and Recipes”. Then, the ilustrations, diagramming and revision of Portuguese were included. The validation stage had seven judges in a round and, after evaluation, obtained a 97% level of agreement between them. Conclusion: A nutrition book on the prevention of skin cancer for lay people was developed and validated, in printed and digital formats (e-book).